Real-time shadow casting using fake soft shadow volume with stencil buffer - 450856 Lee, Kong Weng (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2006